Relationship marketing on social software platforms - Loureiro, S. M. C.; Sarmento, E. M. (The Routledge handbook of consumer behaviour in hospitality and tourism, 2017)
Relationship marketing strategies are typically designed to gather information in order to help firms to identify and retain customers or guests. Firms organize relationship marketing programmes, described as ‘the ongoing process of engaging in cooperative and collaborative activities and programmes with immediate and end-user customers to create or enhance mutual economic value at reduced cost’ (Parvatiyar and Sheth 2000: p. 9). Examples of programmes include: (1) loyalty card programmes, (2) company credit cards, (3) opting in for personalized offers delivered via mailing and (4) via e-mail lists, and (5) rebate offers (Noble and Phillips 2004).